Effect of Investment Decisions, Funding Decisions, and Dividend Policy on the Value of the Company - Susanto, Michela Yuanita Putri; Mujiyati, Mujiyati (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to empirically examine the effect of investment decisions, funding decisions, and dividend policy on the value of the company. In this study using quantitative research. The Data used in this study are secondary data. The population in this study is a list of Sharia stock indices listed on The Jakarta Islamic Index (JII) in 2018-2022. Sampling method using purposive sampling. The number of samples as many as 66 companies. The method of analysis conducted in this study using statistical Application Program tools: Statistical Product and Service Solutions (SPSS). The results of this study are that investment decisions affect the value of the company, while funding and dividend policy decisions do not affect the value of the company.